The AP2/ERF Transcription Factor DRNL Modulates Gynoecium Development and Affects Its Response to Cytokinin - Durán-Medina, Yolanda; Serwatowska, Joanna; Reyes-Olalde, J. Irepan; de Folter, Stefan; Marsch-Martínez, Nayelli (Frontiers in Plant Science, 2017)
The gynoecium is the female reproductive system in flowering plants. It is a complex structure formed by different tissues, some that are essential for reproduction and others that facilitate the fertilization process and nurture and protect the developing seeds. The coordinated development of these different tissues during the formation of the gynoecium is important for reproductive success. Both hormones and genetic regulators guide the development of the different tissues. Auxin and cytokinin in particular have been found to play important roles in this process. On the other hand, the AP2/ERF2 transcription factor BOL/DRNL/ESR2/SOB is expressed at very early stages of aerial organ formation and has been proposed to be a marker for organ founder cells. In this work, we found that this gene is also expressed at later stages during gynoecium development, particularly at the lateral regions (the region related to the valves of the ovary). The loss of DRNL function affects gynoecium development. Some of the mutant phenotypes present similarities to those observed in plants treated with exogenous cytokinins, and AHP6 has been previously proposed to be a target of DRNL. Therefore, we explored the response of drnl-2 developing gynoecia to cytokinins, and found that the loss of DRNL function affects the response of the gynoecium to exogenously applied cytokinins in a developmental-stage-dependent manner. In summary, this gene participates during gynoecium development, possibly through the dynamic modulation of cytokinin homeostasis and response.